Integration of ternary I-III-VI quantum dots in light-emitting diodes - Islas-Rodriguez, Nery; Muñoz, Raybel; Rodriguez, Jose A.; Vazquez-Garcia, Rosa A.; Reyes, Martin (Frontiers in Chemistry, 2023)
Ternary I-III-VI quantum dots (TQDs) are semiconductor nanomaterials that have been gradually incorporated in the fabrication of light-emitting diodes (LEDs) over the last 10 years due to their physicochemical and photoluminescence properties, such as adequate quantum yield values, tunable wavelength emission, and easy synthesis strategies, but mainly because of their low toxicity that allows them to be excellent candidates to compete with conventional Cd-Pb-based QDs. This review addresses the different strategies to obtain TQDs and how synthesis conditions influence their physicochemical properties, followed by the LEDs parameters achieved using TQDs. The second part of the review summarizes how TQDs are integrated into LEDs and white light-emitting diodes (WLEDs). Furthermore, an insight into the state-of-the-art LEDs development using TQDs, including its advantages and disadvantages and the challenges to overcome, is presented at the end of the review.